Pengaruh Sanksi administrasi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Armena, Sherli Oktavia; Maison, Witra; Wahyuni, Lili (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to investigate the impact of tax administration penalties on the compliance behavior of motor vehicle taxpayers. It employs a quantitative research approach, focusing on registered motor vehicle taxpayers at the Solok City Samsat office. Data collection involves a Non-Probability sampling method, with a sample size of 100 respondents. Analysis is conducted using outer and inner models through SmartPLS 3.0 software. The findings indicate that tax administration sanctions significantly influence the compliance of motor vehicle taxpayers.